Semantic extensions of Green Colour Terms in Contemporary English and Ukrainian Fiction - Lukianets, Halyna (My University, 2018)
The analysis of semantic properties of green/зелений colour in the English and Ukrainian languages conducted on the basis of dictionary entries and linguistic corpora data shows how colour categorization is shaped in language and fiction by both nation's common cognitive universals and their socio-cultural evolutionary processes. Corpora data analysis shows semantic extensions of green colour terms in fiction, which are explained in terms of individual authors' cognitive shifts within universal physiological parameters. Expressing personal emotions and implied pragmatic aims writers either create new colours or makes semantic shifts in the existing ones. Metaphors, metonymies, and similes serve basis to create extended green/зелений colour meanings. Synaesthetic shifts of colour perception also enrich colour semantics. Structural extensions of green colour are the combinations of colour term with quality or quantity modifier, which not only denote physical properties of colour, but also show colour emotional and psychological value for the speaker or writer. Аналіз семантичних властивостей green / зеленого кольору англійською та українською мовами, проведений на основі словникових записів та даних лінгвістичних текстів, показує, як здійснюється формування кольорової класифікації у мові згідно як із загальними когнітивними універсалами нації, так і їх соціокультурними еволюційними процесами. Аналіз даних показує семантичне розширення зелених колірних термінів у художніх текстах, які пояснюються в термінах когнітивних зрушень окремих авторів у межах універсальних фізіологічних параметрів. Виражаючи особисті емоції та прагматичні цілі, письменники створюють нові кольори або зміщують смислові зміни в існуючих.
Keywords: кафедра іноземних мов професійного спрямування; colour terms; semantic structure; corpus research; колірні терміни; семантична структура; дослідження корпусу; семантичні розширення; названия цветов; семантическая структура; исследования корпуса; семантические расширения